1981
DOI: 10.1254/jjp.31.941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl-L-carnosine aluminum (CL-1700) on various acute gastric lesions and gastric secretion in rats.

Abstract: Abstract-Effects of a newly synthesized compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…AAHA, has been reported to have a potent inhibitory effect on the formation of various types of acute gastric ulcers or erosions in rats (25). It was proved from the present study that AAHA had a stimulatory effect on the SGP synthesis, particulary the synthesis of highly sulfated glycoproteins at 12 hr after the onset of stress.…”
supporting
confidence: 58%
“…AAHA, has been reported to have a potent inhibitory effect on the formation of various types of acute gastric ulcers or erosions in rats (25). It was proved from the present study that AAHA had a stimulatory effect on the SGP synthesis, particulary the synthesis of highly sulfated glycoproteins at 12 hr after the onset of stress.…”
supporting
confidence: 58%
“…We showed in a previous report that CL 1700 (N-acetyl-L-carnosine aluminum), a new compound, had potent inhibitory effects on the formation of acute gastric lesions in rats (1). CL-1700 is a complex of N-acetyl L-carnosine which is derived from L carnosine and AI(OH)3.…”
Section: Abstract-effectsmentioning
confidence: 97%
“…The dose of CL-1700 used in this study is the one which was effective on several gastric lesions in rats as shown in previous experiments (1). The doses of L-carnosine, N-acetyl-L-carnosine, and AI(OH)3 were selected according to the ratio of each of their molecular weights to the molecular weight of CL-1700 according to the composition of C L-1700.…”
Section: Abstract-effectsmentioning
confidence: 99%
“…We have reported that CL-1700 (N acetyl-L-carnosine aluminum) has a potent antiulcer effect on both acute and chronic types of gastric ulcers in rats (1). In addition, we found that the effects of CL-1700 are much more potent than its constituents, L carnosine, N-acetyl-L-carnosine or AI(OH)3, to inhibit the development of different forms of induced acute gastric ulcers (2).…”
mentioning
confidence: 90%